Autoantibodies against cytochrome P450 side-chain cleavage enzyme in dogs (Canis lupus familiaris) affected with hypoadrenocorticism (Addison’s disease) - Boag, A; Christie, M; McLaughlin, K; Syme, H; Graham, P; Catchpole, B (Public Library of Science, 2015)
Canine hypoadrenocorticism likely arises from immune-mediated destruction of adrenocortical tissue, leading to glucocorticoid and mineralocorticoid deficiency. In humans with autoimmune Addison’s disease (AAD) or autoimmune polyendocrine syndrome (APS), circulating autoantibodies have been demonstrated against enzymes associated with adrenal steroid synthesis. The current study investigates autoantibodies against steroid synthesis enzymes in dogs with spontaneous hypoadrenocorticism. Coding regions of canine CYP21A2 (21-hydroxylase; 21-OH), CYP17A1 (17-hydroxylase; 17-OH), CYP11A1 (P450 side-chain cleavage enzyme; P450scc) and HSD3B2 (3β hydroxysteroid dehydrogenase; 3βHSD) were amplified, cloned and expressed as 35S-methionine radiolabelled recombinant protein. In a pilot study, serum samples from 20 dogs with hypoadrenocorticism and four unaffected control dogs were screened by radio-immunoprecipitation assay. There was no evidence of reactivity against 21-OH, 17-OH or 3βHSD, but five dogs with hypoadrenocorticism showed immunoreactivity to P450scc compared with controls. Serum samples were subsequently obtained from 213 dogs diagnosed with hypoadrenocorticism and 110 dogs from a hospital control population. Thirty control dogs were randomly selected to establish a threshold for antibody positivity (mean + 3 × standard deviation). Dogs with hypoadrenocorticism were more likely to be P450scc autoantibody positive than hospital controls (24% vs. 1.2%, respectively; p = 0.0016). Sex was significantly associated with the presence of P450scc autoantibodies in the case population, with 30% of females testing positive compared with 17% of males (p = 0.037). Significant associations with breed (p = 0.015) and DLA-type (DQA1*006:01 allele; p = 0.017) were also found. This cross-sectional study indicates that P450scc autoantibodies are present in a proportion of dogs affected with hypoadrenocorticism.